Community pharmacists’ use, perception and knowledge on dietary supplements: a cross sectional study - Josipa Bukic (Pharmacy Practice, 2021)
Background: Pharmacists are commonly tasked with recommending the appropriate dietary supplement and advising the patients of their correct and safe use. Previous research, conducted on pharmacy students, showed that they did not always use the evidence based sources of information, with personal use identified as a significant predictor influencing the decision to recommend a supplement.